2013
DOI: 10.3329/ptcb.v23i1.15567
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hormonal Composition, Type of Explant and Light Condition on Callus Production in Periwinkle (Catharanthus roseus L.)

Abstract: Periwinkle plant contains different indole alkaloids such as Ajmalicine, Vincristine and Vinblastine that have many medicinal applications. An approach to produce these compounds is made through cell culture. Therefore, it seems that optimization of callus culture is necessary for this goal. So, in this experiment 16 hormonal treatments, 2 types of explants and 2 light conditions were investigated. Maximum callus percentage fresh and dry weight were obtained from root explants with 1.5 mg/l NAA and 0.1 mg/l Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Light signals are absorbed and transformed via light receptors in plants, so plants metabolism and development can be regulated by light (Chory, 2010; Eckstein, Zieba, & Gabryś, 2012; Gyula, Schafer, & Nagy, 2003). Other studies have shown that light affects the callus formation of periwinkle ( Catharanthus roseus L.) (Akhar & Bagheri, 2013). In this study, we found that the effects of adventitious bud regeneration from leaf explants were affected by light too.…”
Section: Discussionmentioning
confidence: 97%
“…Light signals are absorbed and transformed via light receptors in plants, so plants metabolism and development can be regulated by light (Chory, 2010; Eckstein, Zieba, & Gabryś, 2012; Gyula, Schafer, & Nagy, 2003). Other studies have shown that light affects the callus formation of periwinkle ( Catharanthus roseus L.) (Akhar & Bagheri, 2013). In this study, we found that the effects of adventitious bud regeneration from leaf explants were affected by light too.…”
Section: Discussionmentioning
confidence: 97%